RESPONS PETANI TERHADAP TEKNOLOGI PENGENDALIAN PENYAKIT BUSUK BUAH DENGAN AGENS HAYATI DI KAWASAN AGROWISATA DESA SERANG KECAMATAN KARANGREJA KABUPATEN PURBALINGGA - Harsoyo, Harsoyo; Putra, Asep Mulyana Dian Dwi; Witjaksono, Roso (Berkala Ilmiah AGRIDEVINA, 2017)
This research was to find out the farmers response and the influencing factors of fruit rotcontrol technology with biological agent. The basic method used was analyticaldescriptive with survey technique.The location selected in the area of agrotourism villageof Serang, Karangreja, Purbalingga Regency. Serang village is divided into five hamlets:Serang, Brobahan, Rejadadi, Kaliurip Gunung, and Gunung Malang. On these research,the sample was taken by simple random technique with took 12 respondents at eachvillage district, so that was resulted 60 farmers. The data was analyzed by proportion testand multiple linear regression analysis test. The result showed that the majority offarmers had intermediate response to the fruit rot disease control technology usingbiological control agents. The age and education of farmers affected the farmersresponse possitively, while the farm size, perception, motivation, and the role ofinstructor had been no effect.